EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR KOGNITIF (JENIS PENGETAHUAN) SISWA PADA MATERI SISTEM PERNAPASAN DI KELAS XI SMA NEGERI 16 MAKASSAR - Mutia; Oslan Jumadi; Andi Rahmat Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of the Jigsaw cooperative learning model on students’ learning outcomes based on knowledge dimensions in the respiratory system topic at SMA Negeri 16 Makassar. The study employed a pre-experimental method using a one-group pretest-posttest design. The sample consisted of students from class XI A2 selected through cluster sampling. Data were collected using a validated and reliable multiple-choice test and analyzed using N-Gain and Wilcoxon Signed Rank Test. The results showed a significant difference between pretest and posttest scores, indicated by a Z value of 5.0119, which was higher than the Z-table value of 1.96. Analysis of learning outcomes based on knowledge dimensions revealed different levels of improvement. Procedural knowledge achieved the highest N-Gain score (0.71), followed by metacognitive knowledge (0.70), conceptual knowledge (0.52), and factual knowledge (0.20). These findings indicate that the Jigsaw cooperative learning model is effective in improving students’ learning outcomes, particularly procedural and metacognitive knowledge. Therefore, the Jigsaw learning model can be used as an alternative instructional strategy to improve students’ understanding and active participation in biology learning.